An annotated and illustrated checklist of the porcelain crabs of Panama (Decapoda: Anomura) - de Azevedo Ferreira, Luciane Augusto; Anker, Arthur (Zootaxa, 2021)
The present study is the first exhaustive checklist of porcelain crabs (Porcellanidae) distributed on the Pacific and Atlantic (Caribbean) coasts of Panama, based on literature records and material collected between 2006 and 2019. The Panamanian porcellanid fauna is currently composed of a total of 76 species, with 26 species reported from the Caribbean coast, 45 species reported from the Pacific coast, and five species reported from both sides of the Central American Isthmus (Isthmus of Panama). In other words, the Caribbean and Pacific coasts of Panama each harbour, respectively, 31 and 50 species of porcellanid crabs. However, this total includes two problematic porcellanid records from Panama, viz. Clastotoechus nodosus (Streets, 1872) and Petrolisthes brachycarpus Sivertsen, 1933, as well as a putatively undecribed taxon reported as Pachycheles sp. The following four species are recorded for the first time from Panama, viz. Euceramus panatelus Glassell, 1938, Pachycheles riisei (Stimpson, 1859) [also being new for Mexico], Petrolisthes dissimulatus Gore, 1983 and P. tonsorius Haig, 1960. In addition, Minyocerus kirki Glassell, 1938 is newly recorded from Colombia, extending its previously known distributional range significantly southwards. Most species are illustrated in colour, several for the first time, based on material from Panama or other localities. At least 20 further species (16 in the Atlantic, 5 in the Pacific, and 1 in both oceans) are suspected to occur in Panamanian waters, based on their records from the neighbouring Costa Rica and/or Colombia, or their wide distribution in the Caribbean Sea or the tropical eastern Pacific. The presence of several cryptic or pseudocryptic species (at least some of them presumably undescribed), especially in the taxonomically challenging Petrolisthes galathinus (Bosc, 1802) species complex, or the eventual species splitting within some taxa currently seen as transisthmian, will likely further increase the total number of species present in Panama. The porcellanid fauna of Panama is also ecologically remarkably diversified. Most Panamanian porcelain crabs are free-living under rocks, in crevices of rocks, dead coral heads, coralline algae, coral rubble etc., or on mud, among mangrove roots. Euceramus panatelus lives in possibly self-dug burrows in soft mud or muddy sand, whereas its congener E. transversilineatus (Lockington, 1878) may occasionally be found in association with holothuroids. At least 15 further porcellanid species occurring in Panama live in permanent or facultative associations with a variety of other marine organisms, including sponges, cnidarians (octocorals), echinoderms (sea urchins, sea stars, sea cucumbers), polychaetes (parchment worms) and other decapod crustaceans (hermit crabs), making them one of the most attractive groups for studies of symbiosis-related behaviour and evolution.